1996
DOI: 10.1074/jbc.271.12.6651
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Glycerophospholipid-selective Transbilayer Motion Mediated by a Protein in the Endoplasmic Reticulum Membrane

Abstract: A relatively rapid transbilayer motion of phospholipids in the microsomal membrane seems to be required due to their asymmetric synthesis in the cytoplasmic leaflet. Marked discrepancies exist with regard to the rate and specificity of this flip-flop process. To reinvestigate this problem, we have used both spin-labeled and radioactively labeled long chain phospholipids with a new fast translocation assay. Identical results were obtained with both types of probes. Transbilayer motion of glycerophospholipids wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(104 citation statements)
references
References 28 publications
6
97
1
Order By: Relevance
“…In a similar way, a rapid flip-flop has been reported in microsomal membranes at half-times of seconds to minutes (Buton et al, 1996) in a process that has proved to be ATPindependent and protein-mediated. It has been suggested that this flipping machinery could translocate most, if not all, of the phospholipid classes across the bilayer non-vectorially (Kol et al, 2002).…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…In a similar way, a rapid flip-flop has been reported in microsomal membranes at half-times of seconds to minutes (Buton et al, 1996) in a process that has proved to be ATPindependent and protein-mediated. It has been suggested that this flipping machinery could translocate most, if not all, of the phospholipid classes across the bilayer non-vectorially (Kol et al, 2002).…”
Section: Resultssupporting
confidence: 56%
“…The transverse distribution of phospholipids in the ER, on the other hand, is still a matter of debate after conflicting observations (Devaux, 1993). Nevertheless, recent publications suggest that the distribution of most phospholipid classes in the ER is largely symmetrical (Buton et al, 1996;Kol et al, 2002). Thus it is important to view the biosynthesis of PS and PE in the biogenic membrane, ER, as being an asymmetric process that results in the insertion of new lipids into the cytoplasmic leaflet.…”
Section: Introductionmentioning
confidence: 99%
“…4 and 2A, there is a general trend that the membrane-insertion efficiency is higher when the alkyl side chain is in the lumenal half of the H segment (i.e., the asymmetry in the ΔG app curves correlates with the membrane orientation of the H segment), suggesting that it reflects an asymmetry in either the ER membrane or the Sec61 translocon. Although data are scarce, the ER is thought not to have a strong asymmetry in lipid composition between the two leaflets (17,18). Therefore, it is more likely that the origin of the asymmetry is to be sought in the translocon.…”
Section: Membrane-insertion Characteristics Of Polar Aromatic Side Chmentioning
confidence: 99%
“…This could be mediated by the activation of the scramblase, but, alternatively, SM could £ip across the membrane in a more proximal part of the secretory pathway. Indeed, evidence has been provided for a bidirectional translocation of phospholipids across the ER membrane, whereby SM translocation was slower than that of the glycerophospholipids [245,246]. Whether this rapid £ip-£op is due to a`£ippase' or to non-bilayer structures in the ER membrane has been debated for years [65].…”
Section: Transbilayer Translocationmentioning
confidence: 99%